Acute torrential mitral regurgitation during transcatheter aortic valve replacement: a case report - Yoshiyuki Yamashita; Hiromichi Sonoda; Tomoki Ushijima; Akira Shiose (Surgical Case Reports)
Abstract Background Transcatheter aortic valve replacement (TAVR) is a minimally invasive approach to aortic valve replacement. However, critical cardiovascular collapse can occur during the procedure for various reasons. Case presentation A 90-year-old man with severe aortic stenosis and left circumflex artery stenosis developed acute torrential mitral regurgitation (MR) during TAVR. The valve deployment process induced left ventricular dyssynchrony due to left bundle-branch block and myocardial ischemia in the left circumflex artery region with torrential MR. Transesophageal echocardiography clearly demonstrated the mechanisms of MR, which was successfully bailed out by left ventricular pacing and intra-aortic balloon pumping. Conclusions MR can be seriously exaggerated by various and complicated mechanisms during TAVR and should be rapidly assessed and appropriately managed depending on its mechanisms.